Age estimation based on tooth cementum annulations using light and phase contrast microscope - Apsara, Apsara; Nayak, Sushruth (Journal of Neonatal Surgery, 2025)
Background: This study aimed to compare the estimated age with the actual age by analysing cementum incremental lines using light and phase contrast microscopy Methodology: Conducted in the Department of Oral and Maxillofacial Pathology and Oral Microbiology at Maharishi Markandeshwar (Deemed to be University) Mullana, Ambala, the study utilized 40 extracted teeth (20 males and 20 females), that were stored 10% formalin. Longitudinal ground sections were prepared by using a lathe - cutting machine followed by hand-trimming on the Arkansas stone. These ground sections were mounted with DPX and examined under both light and phase contrast microscopes simultaneously then these slides were transferred to the computer monitor from microscopes under 40x magnification by using NIS Element software. Cementum displayed alternating dark and bright bands, each pair representing a single annulation was counted as one and added at the end with tooth eruption age to estimate the actual age of an individual. Results: The connection between the actual age and phase-contrast microscopy readings was stronger (r = 0.938, p = 0.0001) compared to light microscopy (r = 0.677, p = 0.0001). In male subjects the phase contrast microscopy showed slight underestimation of age (actual: 25.20, estimated: 23.20, p = 0.001), whereas light microscopy understated age even more (actual: 25.20, estimated: 20.75, p = 0.005). Phase contrast microscopy revealed no variation of age in females (actual: 18.80, estimated: 18.85, p = 0.942), but light microscopy revealed understated age (actual: 18.80, estimated: 17.00, p = 0.181). These results suggest that while phase contrast microscopy was more accurate in predicting the actual age, its dependability is impacted by gender variations as we can see more disparities in male samples. Conclusion: The study confirms the stronger association between the cementum annulations and the chronological age, with phase contrast microscopy showing better accuracy as compared to light microscopy